EFEKTIVITAS PEMBELAJARAN BERBASIS SOCIO-SCIENTIFIC ISSUES (SSI) DAN NATURE OF SCIENCE (NOS) DALAM MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA - Sholihath, Lia Laelatul; Ismail, Agus Yadi (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
Scientific literacy is an essential 21st-century competence that reflects students’ ability to understand, apply, and evaluate scientific knowledge in real-life contexts. However, the scientific literacy achievement of Indonesian students remains relatively low, as reflected in the results of the Programme for International Student Assessment (PISA). One of the main contributing factors to this condition is science learning practices that are still predominantly focused on rote memorization of concepts, place limited emphasis on understanding the Nature of Science, and lack relevant social contexts. This article aims to comprehensively examine the effectiveness of the Nature of Science (NOS) and Socio-Scientific Issues (SSI) approaches in enhancing students’ scientific literacy through a Systematic Literature Review (SLR) method. The literature analyzed includes national and international journal articles addressing scientific literacy, the implementation of NOS, and SSI-based science learning. The synthesis of the reviewed studies indicates that explicitly and reflectively implemented NOS instruction significantly contributes to strengthening students’ epistemological understanding of science and critical thinking skills. Meanwhile, the SSI approach has been shown to be effective in improving contextual scientific literacy, with moderate gains based on N-Gain analysis and highly positive student learning responses, particularly in environmental-related issues. Furthermore, the findings suggest that the effectiveness of NOS and SSI is optimized when supported by innovative instructional models and authentic assessments that comprehensively measure the content, process, and contextual dimensions of science learning. Therefore, the integration of NOS and SSI is recommended as a comprehensive pedagogical strategy to strengthen scientific literacy among Indonesian students. ABSTRAKLiterasi sains merupakan kompetensi esensial abad ke-21 yang mencerminkan kemampuan peserta didik dalam memahami, menggunakan, dan mengevaluasi pengetahuan sains dalam konteks kehidupan nyata. Namun, capaian literasi sains peserta didik di Indonesia masih relatif rendah, sebagaimana tercermin dalam hasil Programme for International Student Assessment (PISA). Salah satu faktor utama penyebab kondisi tersebut adalah praktik pembelajaran IPA yang masih berorientasi pada hafalan konsep, kurang menekankan pemahaman hakikat sains, serta minim konteks sosial yang relevan. Artikel ini bertujuan untuk mengkaji secara komprehensif efektivitas pendekatan Nature of Science (NOS) dan Socio-Scientific Issues (SSI) dalam meningkatkan literasi sains peserta didik melalui metode Systematic Literature Review (SLR). Literatur yang dianalisis meliputi artikel nasional dan internasional yang membahas literasi sains, implementasi NOS, dan pembelajaran berbasis SSI. Hasil sintesis menunjukkan bahwa pembelajaran NOS yang diterapkan secara eksplisit dan reflektif berkontribusi signifikan dalam memperkuat pemahaman epistemologis sains dan kemampuan berpikir kritis siswa. Sementara itu, pendekatan SSI terbukti efektif dalam meningkatkan literasi sains secara kontekstual, dengan peningkatan kategori sedang berdasarkan analisis N-Gain serta respons belajar siswa yang sangat positif, khususnya pada isu lingkungan. Temuan lain menunjukkan bahwa efektivitas NOS dan SSI akan optimal apabila didukung oleh model pembelajaran inovatif dan asesmen autentik yang mampu mengukur dimensi konten, proses, dan konteks sains secara terpadu. Dengan demikian, integrasi NOS dan SSI direkomendasikan sebagai strategi pedagogis komprehensif untuk memperkuat literasi sains peserta didik di Indonesia.